Beyond the Law: Exploring the Moral and Philosophical Dimensions of Pancasila in Promoting a Human Rights Culture in Indonesia - Nandarista Tama Aullia Syahrani; Tri Wahyu Ningsih; Asmak Ul Hosnah (HM Publisher, 2025)
This research delves into the moral and philosophical dimensions of Pancasila, Indonesia's national philosophy, and its potential to foster a robust human rights culture in the country. It examines how the five principles of Pancasila, which encompass divinity, humanity, unity, democracy, and social justice, can shape individual and collective attitudes toward human rights, transcending legal frameworks. This study employs a qualitative approach, utilizing a combination of document analysis, case studies, and historical and contemporary literature review. The research analyzes relevant legal documents, including the Indonesian Constitution and human rights laws, alongside philosophical interpretations of Pancasila and its application in Indonesian society. The study reveals that Pancasila's inherent values align with the core principles of human rights, emphasizing human dignity, justice, and equality. By promoting these values, Pancasila can foster a sense of responsibility and respect for human rights at all levels of society. However, the study also identifies challenges in fully realizing this potential, including socio-cultural barriers, historical legacies, and varying interpretations of Pancasila. In conclusion, Pancasila offers a powerful moral and philosophical framework for cultivating a human rights culture in Indonesia. By strengthening the understanding and application of Pancasila's principles, Indonesia can promote a more just and equitable society that upholds the rights of all its citizens.